The journey from child to scientist : integrating cognitive development and the education sciences - Carver, Sharon M.; Shrager, Jeff (American Psychological Association, 2012)
"The impulse to investigate the natural world is deeply rooted in our earliest childhood experiences. This notion has long guided researchers to uncover the cognitive mechanisms underlying the development of scientific reasoning in children. Until recently, however, research in cognitive development and education followed largely independent tracks. A major exception to this trend is represented in the multifaceted work of David Klahr. His lifelong effort to integrate a detailed understanding of children's reasoning and skill acquisition with the role of education in influencing and facilitating scientific exploration has been essential to the growth of these fields. In this volume, a diverse group of stellar contributors follow Dr. Klahr's example in examining the practical implications of our insights into cognitive development for children in the classroom. Authors discuss such wide-ranging ideas as the evolution of "folk science" in young children and the mechanisms that underlie mathematical understanding, as well as mental models used by children in classroom activities. The volume's lessons will have profound implications for STEM education, and for the next generation of scientists"--Publicity materials. (PsycINFO Database Record (c) 2012 APA, all rights reserved).